Research and education for ethnic-racial relations in children education: a fight against the silence noise - Nanci Helena Rebouças Franco; Fernando Ilidio da Silva Ferreira (Universidade Federal de Santa Catarina, 2017)
This article aims to analyse the importance of education for ethnic-racial relations in early childhood education, based on data collected in Salvador (Brazil) and does a counterpoint with a research experience in Braga (Portugal). From a theoretical and methodological point of view, it is based on a qualitative exploratory approach, with the use of bibliographical and documentary research and critical incidents. The results show that there is a talk of children about race relations, the silence of adults in the space of family and school. In this context, education in diversity poses as a challenge / possibility of pedagogical practice promoting equality in Early Childhood Education, in the perspective of understanding children as historical, social, cultural and rights-bearing subjects and participants on the construction of a society more humane and more equitable.